2012
DOI: 10.1093/bjsw/bcs166
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Causes of Stress in Social Work: Sources of Job Demands, Control and Support in Personalised Adult Social Care

Abstract: Social workers in adult social care are at particular risk of job-related stress, although the contribution of different organisational and policy changes to this phenomenon is subject to debate. This paper explores a theoretical framework from the occupational psychology literature (the Job Demand / Control Model) to identify the characteristics of those most at risk of stress, in a sample of 249 social workers and other care managers working in English adult social services from the Individual Budget (IB) pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 27 publications
0
25
0
Order By: Relevance
“…LTC workers' participating in this study scored on average 70 on the decision latitude scale (control), 34 on the psychological job demand scale (demand), 5.9 on the job insecurity scale and 24.4 on the social support scale. Within the literature, only one study employing similar measures was identified (Wilberforce et al, 2014); this focused primarily on less qualified care workers in England and on LTC workers employed as personal assistants to care users with personal budgets. The findings of our study resonate with those of Wilberforce and colleagues, with LTC workers participating in LoCS scoring similarly on the decision latitude scale (70 compared with 69.5); lower on the psychological job demand scale (34 compared with 37.2) and similarly on the social support scale (24.4 compared with 25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LTC workers' participating in this study scored on average 70 on the decision latitude scale (control), 34 on the psychological job demand scale (demand), 5.9 on the job insecurity scale and 24.4 on the social support scale. Within the literature, only one study employing similar measures was identified (Wilberforce et al, 2014); this focused primarily on less qualified care workers in England and on LTC workers employed as personal assistants to care users with personal budgets. The findings of our study resonate with those of Wilberforce and colleagues, with LTC workers participating in LoCS scoring similarly on the decision latitude scale (70 compared with 69.5); lower on the psychological job demand scale (34 compared with 37.2) and similarly on the social support scale (24.4 compared with 25).…”
Section: Discussionmentioning
confidence: 99%
“…There remains a paucity of research on the psychological wellbeing of LTC workers, despite ongoing attention to emotional burnout, job demand and emotional distress among human services' practitioners (Maslach and Jackson, 1984). The majority of UK studies of these topics focus on professionally qualified staff such as social workers (Hussein et al, 2014a and2014b;Manthorpe et al, 2014), mental health professionals (Evans et al, 2006) and nurses (Gama et al, 2014;Skirrow and Hatton, 2007;Woodhead et al, 2016), with relatively few studies focusing on LTC workers who provide direct or hands-on personal and emotional support to a variety of care users (Wilberforce et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…These include Mental Health Act reforms in which statutory duties that were previously the preserve of social work were opened to a wider range of health and allied health professions, contributing to a 'reduced status' compared to other disciplines (Bailey and Liyanage, 2012). Moreover, a widely reported finding is that the managerialist approaches to risk have further eroded the autonomy and professional judgement of social workers relative to other professions (Wilberforce et al, 2014). Although more optimistic accounts exist (Evans, 2013), and social work undoubtedly continues to play a leadership role amongst Approved Mental Health Practitioners (AMHPs), the dominant narrative is of a professional specialism that is marginalised and misunderstood relative to other disciplines (All Party Parliamentary Group on Social Work, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Within the Job demands and resources (JD-R) theory, demands are physical, social or organizational aspects of the job that require sustained physical or mental effort and these are therefore associated with certain physiological and psychological costs (Bakker & Demerouti, 2007). Role overload, role conflict, time pressure, level of concentration, and to depend on other's job could be included within this category (Wilberforce et al, 2014). Although relationships between demands and outcomes might be more complex, several me-ta-analysis gave support to the negative link between job demands and outcomes since these demands evoke negative emotions and attitudes.…”
Section: Introductionmentioning
confidence: 99%
“…Although relationships between demands and outcomes might be more complex, several me-ta-analysis gave support to the negative link between job demands and outcomes since these demands evoke negative emotions and attitudes. In helping professions the negative role of job demands on job outcomes (e.g., quality of care) and attitudes (e.g., job satisfaction) have been consistently found (Van Bogaert, Timmermans, Weeks, Heusden, Wouters, & Franck, 2014;Wilberforce et al, 2014). In social work, several studies also reported negative relationships between job demands such as job pressure or high intensity and job satisfaction (Allen, Lambert, Pasupuleti, Cluse-Tolar, & Ventura, 2004).…”
Section: Introductionmentioning
confidence: 99%